Targeted Athletic Training Improves the Neuromuscular Performance in Terms of Body Posture From Adolescence to Adulthood – Long-Term Study Over 6 Years - Ludwig, Oliver; Kelm, Jens; Hammes, Annette; Schmitt, Eduard; Fröhlich, Michael (Frontiers in Physiology, 2018)
Poor posture in childhood and adolescence is held responsible for the occurrence of associated disorders in adult age. This study aimed to verify whether body posture in adolescence can be enhanced through the improvement of neuromuscular performance, attained by means of targeted strength, stretch, and body perception training, and whether any such improvement might also transition into adulthood. From a total of 84 volunteers, the posture development of 67 adolescents was checked annually between the age of 14 and 20 based on index values in three posture situations. 28 adolescents exercised twice a week for about two hours up to the age of 18, 24 adolescents exercised continually up to the age of 20. Both groups practiced other additional sports for about 1.8 hours/week. 15 persons served as a non-exercising control group, practicing optional sports of about 1.8 hours/week until the age of 18, after that for 0.9 hours/week. Group allocation was not random, but depended on the participants’ choice. A linear mixed model was used to analyze the development of posture indexes among the groups and over time and the possible influence of anthropometric parameters (weight, size), of optional athletic activity and of sedentary behavior. Differences in posture index values among the groups and within each group were verified using repeated ANOVA. The post hoc pairwise comparison was performed applying the Scheffé test. The significance level was set at 0.05. The group that exercised continually (TR20) exhibited a significant posture parameter improvement in all posture situations from the second year of exercising on. The group that terminated their training when reaching adulthood (TR18) retained some improvements, such as conscious straightening of the body posture. In other posture situations (habitual, closed eyes), their posture results declined again from age 18. The effect sizes (ƞ²=0.12 - ƞ²=0.19) represent moderate to strong effects. The control group did not exhibit any differences. Anthropometric parameters, additional athletic activities and sedentary behavior did not influence the posture parameters significantly. An additional athletic training of 2 hours per week seems to have the potential to improve body posture in symptom free adolescents and young adults.